Reviewing The Legal Status of the Joint Ministerial Decrees in Indonesian State Administrative Law - Suwiryo Prawira; Dion Nupianto (Journal of Legal Contemplation, 2026)
The implementation of state governance based on the concept of a material rule of law requires discretion as an adaptive mechanism to prevent stagnation and legal vacuum. This is manifested in practice in the form of the government's authority (freies ermessen) in making decisions. As is practiced in Indonesia, for example, several government officials or ministers under certain legal circumstances issue a single decision simultaneously called a "joint decision of government officials." The problem that must be highlighted lies in the nature of the product of "decisions," which tend to regulate, and sometimes even limit human rights. In theory, these characteristics should be identical to legal products of legislation (regeling). The actual meaning of "decisions" and the legal status of joint ministerial decrees in state administrative law will be the issues addressed in this article. This research is a normative legal research, using both a statutory and conceptual approach. The research results reveal that, in Indonesian state administrative law, a joint ministerial decree is included in the category of other types of legislation if it is based on the Law on the Formation of Legislation, so that even though the nomenclature used is "decision", if the material contains elements of restrictions and regulations, then it is categorized as a regulation. It may seem anomalous, but the legal basis is clear, that after the presence of Law Number 12 of 2011, the use of the nomenclature "decision" for a regulatory provision is no longer justified.